Place of the United States Secretary of States in the power system and formation of the country external course (XX - at the beginning of XXI century): historical backgraund - Tetiana Klynina (Cхід, 2020)
The article deals with the position of the head of the US Department of State - Secretary of State in the US government system and his role in shaping the country's foreign policy. The author emphasizes the lack of basic research on this topic and the availability of only factual material on the activities of the Secretaries of State in various historical periods of American history. It is noted that the Secretary of State's position is not quite similar to that of the Minister of Foreign Affairs, since he serves in this country in two roles: as the President's foreign policy chief adviser and as the head of a vast diplomatic corps. The author points out that the role and status of the Secretary of State is not regulated at the constitutional level and provides a list of powers of the Secretary of State and notes their extension since the creation of such office in 1789. The author points out that, before the Second World War, in most cases, in the tandem, the President-Secretary of State was the second to formulate the foreign policy of the country and to initiate its implementation, and was able to do justice to the president. Secretaries of State such as R. Lansing, B. Colby, and C. Hughes have enjoyed the trust of their presidents and have had a significant influence on the conduct of American foreign policy. During the presidency of F. Roosevelt and G. Truman, these individuals were themselves Secretaries of State, maximally moving the heads of the State Department to the background, giving them the opportunity to "bring order" not in the foreign policy arena, but in the State Department. It was not positive for the role of the Secretary of State and his Office the adoption of the 1947 Act establishing the National Security Council and the separation of a separate position - the President's national security adviser. From this very moment, the leaders of the National Security Council began to popularize the idea that foreign policy is not just one of the activities of the state, but directly a component of national security. Of course, this has led to increased NNG involvement in the country's foreign policy, which has often led to conflicts between the President's National Security Advisor and the Secretary of State, and the US President himself has not always supported the latter. It is noted that the Secretaries of State under Presidents J. Kennedy, L. Johnson, and R. Nixon, J. Bush Jr. played a rather indirect role in the country's foreign exchange. In contrast, Presidents D. Eisenhower, R. Reagan, B. Clinton and B. Obama respected and acted in tandem with their secretaries of state.